Schedule Making and Implementation of Preventive Maintenance on Fruit Fly Pest Catching Equipment - Adhan Efendi; Ridwan Baharta; Agus Haris Abadi; Pandu Sabirin (VANOS Journal of Mechanical Engineering Education, 2022)
This study aims to schedule and implementation preventive maintenance on fruit fly catching tools with a solar powered Arduino system. Maintenance of these tools is expected to be able to help chili farmers in eradicating fruit fly pests that can cause crop failure for chili farmers. The stages carried out by the research team in the process of making and implementing a maintenance schedule for fruit fly traps. This research is a type of development research. Making a preventive maintenance schedule starts with making observations, then grouping components, making schedules, expert validation and implementation. The data obtained from the observations were analysed qualitatively descriptively. The results showed that: (1) Making a maintenance schedule for fruit fly traps starting from observation, component identification, initial planning, validation and implementation of the maintenance schedule; (2) The implementation of a preventive schedule with inspection and small repair methods is carried out on the main frame and electrical system; (3) Implementation of Inspection on frame manufacturing with a total of 100' Minutes and Small Repair with a total of 80; minutes during a four-month machine maintenance schedule. Meanwhile, the implementation of Inspection on the electrical system with a total of 240 minutes.